2021
DOI: 10.1177/18479790211065558
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the Triage: A dashboard to assess the quality of nurses’ decision-making

Abstract: This paper presents a dashboard for assessing the quality of Triage decision-making process in the assignment of the priority code to patients arriving at an emergency department. The quality is assessed through performance indexes aimed at measuring both the nurses’ accuracy and the presence of nurses’ shared behavior in the Triage assignment process. The theoretical perspective of the cognitive heuristic, that is a cognitive shortcut strategy to make decisions, is the framework to design performance indexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(61 reference statements)
0
1
1
Order By: Relevance
“…Unexpectedly, nurses' work experience was not shown to have a significant impact on the accuracy of triage assessments. This contrasts with previous findings from (Cannavacciuolo et al, 2021;Levis-Elmelech et al, 2022) study, which showed that experience can contribute to more accurate decisionmaking in triage assessments.…”
Section: Discussioncontrasting
confidence: 99%
“…Unexpectedly, nurses' work experience was not shown to have a significant impact on the accuracy of triage assessments. This contrasts with previous findings from (Cannavacciuolo et al, 2021;Levis-Elmelech et al, 2022) study, which showed that experience can contribute to more accurate decisionmaking in triage assessments.…”
Section: Discussioncontrasting
confidence: 99%
“…The development and improvement of triage decision-making skills can be addressed through different educational strategies, supported by clinical experience, and this should serve to improve patient flow in the ED [ 10 – 12 ]. Simulation seems to be more effective than simple lectures in training nurses in triage [ 13 , 14 ]. Nevertheless, a systematic review was held in Iran from 2010 to 2020 to identify the best method for teaching triage and this concluded that a mixed learning approach (workshop, lectures, simulation, and games) was the most effective triage training [ 15 ].…”
Section: Introductionmentioning
confidence: 99%